2007
DOI: 10.1021/la070004i
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nanobubbles on Hydrophobic Surfaces in Water

Abstract: The aim of this paper is to quantitatively characterize the appearance, stability, density, and shape of surface nanobubbles on hydrophobic surfaces under varying conditions such as temperature and temperature variation, gas type and concentration, surfactants, and surface treatment. The method we adopt is atomic force microscopy (AFM) operated in the tapping mode. In particular, we show (i) that nanobubbles can slide along grooves under the influence of the AFM tip, (ii) that nanobubbles can spontaneously for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
243
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(261 citation statements)
references
References 16 publications
14
243
3
1
Order By: Relevance
“…The ice− water bath was used to enhance the dissolved O 2 level in the solution, and the temperature-increasing operation was carried out to generate oxygen bubbles at the solid−liquid interfaces. 14,27 The small contact angle of water on the diatomite (17°, JY-PHb, Jinhe Co.) showed that the diatomite was highly hydrophilic ( Figure S2). BET surface area analysis indicated a specific surface area of 7.4 m 2 /g (ASAP-2010, Micromeritics) for the diatomite.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ice− water bath was used to enhance the dissolved O 2 level in the solution, and the temperature-increasing operation was carried out to generate oxygen bubbles at the solid−liquid interfaces. 14,27 The small contact angle of water on the diatomite (17°, JY-PHb, Jinhe Co.) showed that the diatomite was highly hydrophilic ( Figure S2). BET surface area analysis indicated a specific surface area of 7.4 m 2 /g (ASAP-2010, Micromeritics) for the diatomite.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Surface nanobubbles were generated using temperature variation. 14,27 The stability of O 2 nanobubbles on the hydrophilic particles was investigated hours after oxygen aeration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Research advances in various physical aspects of surface nanobubbles in the past decade include methods of nanobubble generation based on solvent exchange, 20,31−33 temperature gradients, 21,34 the plasmonic effect, 35 and water electrolysis. 36−40 Alcohol−water exchange is proven to be an effective method that can generate a large number of air nanobubbles with high repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…They are surprisingly stable [10,[12][13][14], surviving orders of magnitude longer than the classical diffusive life time. Since their recent discovery, several key observations have been made regarding the 'ideal' conditions for nucleation [15][16][17]. These include the (almost [18,19]) uniqueness for the formation in water, or in solutions containing at least some part water.…”
Section: Introductionmentioning
confidence: 99%